Strategies for Improving Elementary School Teachers' Professional Competence in Remote Regions: A Case Study in Merauke Regency, Papua Province - Adolfina, Adolfina; Rahmawati, Tina (Papanda Publisher, 2025)
This study examines strategies for improving professional competence of elementary school teachers in Merauke Regency, a remote region in Papua Province, Indonesia. The research aims to analyze professional development programs, identify supporting and inhibiting factors, and formulate effective strategies for teacher competence enhancement in geographically challenging contexts. A qualitative case study approach was employed, involving three elementary schools: SD Inpres Mopah Baru, SD Inpres Mangga Dua, and SD Advent Merauke. Data were collected through semi-structured interviews with 44 teachers and 3 school principals, direct observations of school facilities and teaching practices, and document analysis of training records and teacher qualifications. Data analysis followed Miles and Huberman's interactive model, incorporating data reduction, display, and conclusion drawing with triangulation to ensure credibility. Results revealed that professional development programs focus on teacher certification, continuing education, and training participation facilitated by school leadership. Key supporting factors include adequate baseline qualifications, active principal leadership, and collaborative learning cultures. However, significant barriers include limited budgets, time constraints from heavy workloads, inadequate technology infrastructure, and misalignment between teacher specializations and teaching assignments. Schools implemented adaptive strategies combining formal training opportunities with peer mentoring and collaborative learning to overcome resource constraints. The study contributes empirical evidence on teacher professional development in 3T regions and suggests that effective strategies must be context-specific, integrating flexible delivery modes, sustained support mechanisms, and infrastructure investments while leveraging collaborative professional cultures inherent in remote school settings.